2020
DOI: 10.4102/sajbm.v51i1.1675
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in the relationship between innovation and its antecedents

Abstract: Purpose: The aim of this study was to go beyond measurement invariance and assess whether innovation and its antecedents relate to each other in the same way for men as for women when using measurement invariant instruments.Design/methodology/approach: The sample represents 52 South African organisations, with 60 employees from each, amounting to 3143 respondents, of which 56.4% were men and 43.6% women. Four instruments, of which the measurement invariance across gender has been determined, were included in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…(Biga-Diambeidou et al, 2021;Roh and Koo, 2019). Men and women show no differences in their innovativeness (Steyn and de Bruin, 2020;Nählinder et al, 2015), Cropley and Cropley (2017) and Schneid et al (2015) found a significant negative impact of gender diversity on innovation performance. The caused of which is a social categorization process, amplified by national culture, whether it is collectivistic or individualistic societies.…”
Section: Literature Reviewmentioning
confidence: 87%
“…(Biga-Diambeidou et al, 2021;Roh and Koo, 2019). Men and women show no differences in their innovativeness (Steyn and de Bruin, 2020;Nählinder et al, 2015), Cropley and Cropley (2017) and Schneid et al (2015) found a significant negative impact of gender diversity on innovation performance. The caused of which is a social categorization process, amplified by national culture, whether it is collectivistic or individualistic societies.…”
Section: Literature Reviewmentioning
confidence: 87%
“…Measurement invariance evaluates whether the innovative work behaviour construct, measured using the IBI, is assessed the same way between gender groups (Sanhokwe & Takawira, 2022). Gender differences have been reported or critiqued in extant literature (see De Bruin & Steyn, 2020). Hence, the need to assess the equivalence of the measure to facilitate valid interpretations.…”
Section: The Present Studymentioning
confidence: 99%
“…Three more articles published in the SAJBM considered differences between men and women as users of technology (Kotze, Anderson, & Summerfield, 2016;Nel & Raleting, 2012) and food products (Priilaid & Horwitz, 2016). Emirati women's experiences of job satisfaction introduced a perspective on women in the Middle East (Ercan, 2018), and the most recent article advances research on women at work by making a sound methodological contribution to quantitative research on women and men (Steyn & De Bruin, 2020a). Furthermore, the above contributions predominantly focused on South African women and workplaces, and there is still a dearth of research on the lived experiences of women at work on the rest of the African continent.…”
mentioning
confidence: 99%